Home visits by community health workers to prevent neonatal deaths in developing countries: a systematic review - Siddhartha Gogia; Harshpal Singh Sachdev (The World Health Organization, 2010)
OBJECTIVE: To determine whether home visits for neonatal care by community health workers can reduce infant and neonatal deaths and stillbirths in resource-limited settings. METHODS: We conducted a systematic review up to 2008 of controlled trials comparing various intervention packages, one of them being home visits for neonatal care by community health workers. We performed meta-analysis to calculate the pooled risk of outcomes. FINDINGS: Five trials, all from southAsia, satisfied the inclusion criteria. The intervention packages included in them comprised antenatal home visits (all trials), home visits during the neonatal period (all trials), home-based treatment for illness (3 trials) and community mobilization efforts (4 trials). Meta-analysis showed a reduced risk of neonatal death (relative risk, RR: 0.62; 95% confidence interval, CI: 0.440.87) and stillbirth (RR: 0.76; 95% CI: 0.65-0.89), and a significant improvement in antenatal and neonatal practice indicators (1 antenatal check-up, 2 doses of maternal tetanus toxoid, clean umbilical cord care, early breastfeeding and delayed bathing). Only one trial recorded infant deaths (RR: 0.41; 0.30-0.57). Subgroup analyses suggested a greater survival benefit when home visit coverage was > 50% (P < 0.001) and when both preventive and curative interventions (injectable antibiotics) were conducted (P= 0.088). CONCLUSION: Home visits for antenatal and neonatal care, together with community mobilization activities, are associated with reduced neonatal mortality and stillbirths in southern Asian settings with high neonatal mortality and poor access to facility-based health care.